Projection of Denmark’s Population 2021-2050 with a focus on Mortality Trends, Longevity, and Multigenerational Workforce - Abid, Mansoor (2022)
The research’s aim is to project the population of Denmark from 2021 to 2050 and see the trends in longevity, mortality in the older ages while comparing them side by side with the official projections for the same time period. The main questions revolve around confirming if longevity is on the rise and mortality on the decline regardless of modelled assumptions of different projections, what are the consequences for the labor force and if immigration or an older workforce can be the solution. We find that Denmark would experience a small change in total population however an increase in the share of older population. Immigration will be beneficial however to very small extent. On the other hand, older workforce has a good potential with their good health, education levels and non-monetary motivations to stay in the workforce. Key areas identified that, if improved, can assist in a better and more feasible multigenerational workforce would be the communication and trust between management and the older employees. Along with that continued education and reskilling for the older employees will also be of paramount importance to make sure that a multigenerational workforce model can work on an organizational level and thus assist in slowing down the effects of aging on the productive population of Denmark.